A Convenient Iodine‐Promoted Synthesis of α‐Ketothioesters. Issue 38 (10th October 2022) - Zhao, Zhengzheng; Gao, Pan; Meng, Lei; Wu, Qingyi; Yuan, Yu
Abstract: An effective and practical synthesis of α‐ketothioesters has been reported for direct oxidative thioesterification of substitutional acetophenones with dimethyl sulfoxide and iodine in the presence of boric acid and acetic anhydride in high yields. According to the control experiments and literatures, the reaction mechanism was proposed to undergo via Pummerer rearrangement. Abstract : We have achieved for the synthesis of α‐ketothioesters from commercially available, inexpensivearylketones under mild conditions. Furthermore, we present the dicarbonylationofamineswithα‐ketothioesters using simple conditions to formα‐ketoamides, which widely present in natural product molecules and also can be used as precursorsfor the synthesis of important compounds.